Psychophysiological responses to overloading and tapering phases in elite young soccer players - Freitas, C. G.; Aoki, M. S.; Franciscon, C. A.; Arruda, A. F. S.; Carling, C.; Moreira, A. (Pediatric Exercise Science, 2014)
This study investigated the effect of a 2-week overloading training phase followed by a 2-week tapering phase on internal training load (ITL), salivary cortisol, stress tolerance, and upper respiratory tract infections symptoms (URTI) in 11 male young soccer players (16.0 ± 0.5 yrs). Ratings of perceived exertion (session- RPE) were taken after each training session (N = 194) to determine ITL. Saliva sampling was conducted at the end of each week and cortisol concentration assessed by ELISA. DALDA and WURSS-21 questionnaires were administered every week to evaluate stress tolerance and severity of URTI respectively. The number of athletes reporting URTI symptoms was recorded. The overloading phase promoted greater ITL and a higher resting cortisol concentration than the tapering phase (P < .05). While no significant changes in stress toler- ance or URTI severity were observed, the number of athletes reporting URTI symptoms was higher during the overloading phase. A significant correlation was observed between symptoms of stress and severity of URTI (rs=-.71; P = .01). The results indicate that an integrated approach using psychological measures (session-RPE and DALDA), self-reports of URTI symptoms, and endocrine responses (cortisol) to training are pertinent for monitoring young soccer players.